Sleep quality of student athletes and non-athletes - the role of chronotype, stress and life satisfaction - Litwic-Kaminska, Kamila; Kotysko, Martyna (Sleep Science, 2020)
Objective There are many internal and external factors that can affect sleep deterioration. The adopted model of the relationship between chronotype, stress, life satisfaction and sleep quality was verified in the study.Material and Methods In total, 335 healthy university students were surveyed using the Morningness-Eveningness Questionnaire, Perceived Stress Scale, Satisfaction with Life Scale and Pittsburgh Sleep Quality Index. The study included two groups: individuals involved in sport activities (student athletes, n=207) and those who declared (in the short form of the International Physical Activity Questionnaire) low physical activity level (non-athlete students, n=128).Results Student athletes were less stressed (p<0.001) and declared higher life satisfaction (p<0.001) and sleep quality (p<0.001) compared to non-athletes. Non-athletes tended to identify the evening hours as their best time for functioning (p<0.001), but the mean results of both groups oscillated around the so-called intermediate type. Despite the differences in mean values, the model invariance for both groups was confirmed, which means that the proposed theoretical model applies equally to student athletes and non-athletes. The path analysis results indicate that chronotype has a direct negative influence on sleep quality (preferring morning hours results in higher sleep quality). However, perceived stress partially mediates this relationship (p<0.001).Discussion Sleep quality should not be considered without taking into account circadian preferences. Effective coping with stress may also be a buffer in reducing sleep problems.
Keywords: Sleep; Stress; Psychological; Circadian Rhythm; Students; Health